The Affect of the Cranial Elektrotherapy on the Dynamic Parameters of Movements - Čupriks, Leonīds; Rudzītis, Andris; Čuprika, Aleksandra; Žilinskis, Leonīds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
It is considered that in sport athletes use the cranial electrotherapy stimulation (CES) to improve the performance and to increase the ability to concentrate before the competition. Based on the previous researches we can conclude that CES is absolutely safe. Therefore, the aim of the current study is to determine the CES affect on the dynamic parameters of movements (power, strength, velocity). Subjects of our study were twenty healthy athletes of luge, bobsled and skeleton. The evaluation of the dynamic parameters of movements was performed before and after CES during the barbell „lift„ in concentric phase of lifting with FiTRODyne Premium device (Slovakia). To analyze data was used Excel program Statistics 3.1.After the CES the parameters of power capacity and the results of strength were improved (α < 0,05). The differences between the time parameters of the controlled exercise before and after CES were not statistically significant (α > 0,05 ), also the improvement of the velocity of controlled exercise is not statistically significant ( α > 0,05 ). The results obtained in the research prove that the affect of 10 minutes of CES partly influence the dynamic parameters of movement.